Information Technology Of Automation Of Life Cycle Of Construction Objects - et.al, Kateryna Kyivska, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The article is devoted to solving an important scientific and practical problem of automation of the life cycle of construction objects. The methodological principles of development of the unified extensible information technology of automation of life cycle of building objects with the use of the generalized model of the building object are offered, the kernel of the model is created on the basis of the basic set of graphic primitives and attributes. The classification of software used at different stages of the life cycle of a construction object and their generalized model is also proposed. In order to optimize the database containing information about the model of the construction object, it is proposed to use the created method of binary data packing